Opioid use and opioid overdose in the Netherlands – a 10 years retrospective study of naloxone administration in Dutch emergency departments - Bram Kok; Joris Holkenborg; Alba van der Have; Brigitte van de Kerkhof – van Bon; Joris Datema; Pieter Veenstra; Djoke Douma-den Hamer; Cornelis Kramers (Emerging Trends in Drugs, Addictions, and Health)
Background: The number of opioid users in the Netherlands has doubled in the last two decades. To assess if the rise in use also means a rise in severe opioid intoxications, we studied the number of opioid intoxications necessitating naloxone administration in Dutch emergency departments during the last 10 years. Methods: a multi-center retrospective cohort study that uses information of Dutch emergency department visits between 2011 and 2020 was conducted. Information on type of opioid, reason for use, and duration of use was collected. A severe opioid intoxication was defined as a patient with an opioid toxidrome in whom a rapid improvement of symptoms occurred after administration of naloxone. Results: Five emergency departments participated in this study. The number of episodes of naloxone administrations was 311 in 292 unique patients. 187 cases were considered a severe opioid intoxication. Mean annual incidence was 19.5 cases with a maximum annual incidence of 28 cases. The opioid mostly involved was oxycodone in 69 cases (37 %); followed by methadone in 41 cases (22 %) and fentanyl in 26 cases (14 %). 127 cases (68 %) were using opioids since >3 months. 176 cases (94 %) were admitted of whom 96 to the intensive care unit. Twenty three cases died within 30 days (12 %). Conclusion: There is no clear increase in naloxone administration in Dutch emergency departments to treat opioid intoxication between 2011 and 2020. The almost twofold increase in prescription opioids in the Netherlands during the study period is not accompanied by an increase in opioid intoxications in the emergency department.